The role of energy recovery from wastes in the decarbonization efforts of the EU power sector. Issue 1 (26th October 2021) - Psomopoulos, Constantinos S.; Kiskira, Kyriaki; Kalkanis, Konstantinos; Leligou, Helen C.; Themelis, Nickolas J.
Abstract: Wastes contain large quantities of energy that can be extracted using a variety of methods. European Union has established a waste‐to‐energy initiative to minimize waste and increase recovery. Τhe EU Landfill Directive promotes more environmental friendly waste management options. Accordingly, EU member states are adopting mechanical‐biological treatment processes, bio‐methanization and waste‐derived fuels. Furthermore, EU is energy‐dependent, as its resources are insufficient to meet rising energy demands, and fossil fuels must be imported in large quantities. Wastes are increasingly produced and have a non‐negligible lower calorific value that are considered as a power source. Findings highlight the role of waste‐to‐energy facilities in meeting a portion of the European Union's energy needs and contributing to the achievement of renewable energy targets. The untapped potential, through specific actions, can increase capacity in EU without threatening the goals for recycling. This work presents the current status of energy recovery in EU and investigates the unutilized potential energy recovery from wastes, considering the currently landfilled quantities. The results showed that even in the worst scenario, the energy recovery and the renewable content are too high to be neglected, supporting the decarbonization efforts and enhance circular economy, in line with EU's Energy Strategy and Paris agreement.